(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless Sensor Network (WSN) is widely researched field which encompasses various revolutionary applications in fields like traffic management, wildlife preservation last but not the least armed forces. The addition of wireless sensor networks in various fields has also increased the security treats that have to be covered while using it. The objectives of this paper is to explore the security relat